Understanding social distancing intention among university students during Covid-19 outbreak: an application of protection motivation theory - Haque, A. K. M. Ahasanul; Karim, Wasiul; Kabir, SMH; Tarofder, Arun Kumar (2020)
The Covid-19 outbreak has clearly pierced the life of humankinds in almost all countries and all members of the society. Understanding and practicing measures for self-protection and maintaining social distance for prevention of transmission of infection are the new guidelines. This study examined decision factors such as perceived severity, susceptibility, response efficacy, self-efficacy and social distancing intention for students in Malaysia in response to the pandemic. The study was conducted following a quantitative research approach. Primary data were collected through Google form and online social media from 256 students studying in International Islamic University Malaysia. For the purpose of the study, Exploratory Factor Analysis and Structural Equation Modeling techniques were performed. The analyses revealed that two variables (response efficacy and self efficacy) of the protection motivation theory were significant predictors of social distancing intention during the ongoing Covid-19 pandemic crisis. However, perceived severity and perceived susceptibility were not significant predictors of intention to engage in social distancing behaviour. The findings demonstrated that PMT was a constructive framework for understanding intention to engage in social distancing behaviour during a pandemic. The findings may help in filling the intention-behavioral gap in relation to social distancing.